2023
DOI: 10.3389/fpubh.2023.1158716
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 experiences of social isolation and loneliness among older adults in Africa: a scoping review

Abstract: ObjectiveSocial isolation and loneliness (SI/L) are considered critical public health issues. The primary objective of this scoping review is to document the experience of SI/L among older adults in Africa during the COVID-19 pandemic, given research gaps in this area. We identified the reasons for SI/L, the effects of SI/L, SI/L coping strategies, and research and policy gaps in SI/L experiences among older adults in Africa during COVID-19.MethodsSix databases (PubMed, Scopus, CINAHL, APA PsycINFO, Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“… 11 , 23 Prior studies have reported the adverse impact of COVID-19 pandemic on health, social connection, economic stability and overall wellbeing of older adults in Nigeria. 24 - 28 Major gaps in these studies are that they lack comprehensive interdisciplinary studies that integrate health, social connection, economic stability, and overall well-being of older individuals. Existing research tends to compartmentalize these aspects, hindering a holistic understanding of the multifaceted challenges faced by older adults during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 23 Prior studies have reported the adverse impact of COVID-19 pandemic on health, social connection, economic stability and overall wellbeing of older adults in Nigeria. 24 - 28 Major gaps in these studies are that they lack comprehensive interdisciplinary studies that integrate health, social connection, economic stability, and overall well-being of older individuals. Existing research tends to compartmentalize these aspects, hindering a holistic understanding of the multifaceted challenges faced by older adults during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Technology-mediated communication compared unfavourably with the “gold standard” of in-person presence in Burholt et al's study of family contacts with older people; telephone, text and video contacts were found to be neither functionally nor emotionally equivalent to embodied, physical co-presence ( 60 , p.1209). Technology is reported as being unable to replace face-to-face social interaction ( 61 ), and maintaining therapeutic relationships via digital interfaces can be difficult ( 53 ). Technology designers have responded to the challenges of producing more satisfactory experiences of technology-mediated communication – as shown in increased provision of video-calling during the pandemic compared to audio-only telephone contact – and through embodied technologies such as the therapeutic social robot, Paro, and HUG, a therapeutic calming device for people with dementia ( 62 ).…”
Section: Introductionmentioning
confidence: 99%
“…More prosaically, but of critical importance, technology fails to address loneliness and social isolation when it does not work due to poor connectivity or it is not available when people do not own devices or have the skills, knowledge or dexterity to use technology, as highlighted by Adedeji et al's scoping review of technology and social isolation and loneliness amongst older people in African countries during the pandemic. Ineffectiveness in that context was associated, in part, with poor infrastructure and the digital divide (lack of internet access, devices, and disposition towards technology ( 61 ). Usability, acceptability and availability are necessary for technologies to be adopted to address loneliness, as is technical competence, with additional difficulties apparent for older adults as well as people digitally “excluded” ( 64 ).…”
Section: Introductionmentioning
confidence: 99%